Effect of nano and macro carbon fillers on flexural properties of glass fiber/epoxy composite laminates. (December 2018) - Deep, Akash; Singh, K K; Rawat, Prashant; Kumar, Chandan; Behera, Rohit Pratyush
Abstract: In this work, symmetrically designed glass fiber composites with epoxy matrices modified with multiwall carbon nanotubes (MWCNTS ) and short carbon fiber fillers (SCFF) have been manufactured using hand layup technique assisted by press molding machine. The flexural test (three point bend test) was performed on MWCNTS reinforced and MWCNTS with short carbon fiber fillers (SCFF) or hybrid reinforced GFRP using Hounsfield H50KS universal testing machine at a strain rate of 1mm/min. The result showed that the addition of nano and macro fillers (i.e. MWCNTS and SCFF) improved flexural strength of GFRP laminate. This increment is more evident in the case of composite filled with MWCNTS (0.5wt %)and SCFF (0.5wt %) both.